Carboxyamido/carbene ligated palladium (II) complex: A versatile catalyst for the synthesis of aryl-substituted heteroarenes. (14th December 2016) - Vishnuvardhan Reddy, Police; Parsharamulu, Thupakula; Annapurna, Manne; Likhar, Pravin R.; Kantam, Mannepalli Lakshmi; Bhargava, Suresh
Graphical Abstract: Carboxy amido/carbene ligated Pd-complex catalyzed Suzuki-Miyaura cross-coupling of aryl-boronic acids with heteroaryl bromides is described. The protocol has a broad substrate scope that includes electron-rich, electron-deficient and sterically hindered arylboronic acids and heteroaryl bromides. The catalytic activity of the catalyst has further investigated in the coupling of 2, 6-dibromopyridine with arylboronic acids. Abstract: Carboxy amido/carbene ligated Pd-complex catalyzed Suzuki-Miyaura cross-coupling of aryl-boronic acids with heteroaryl bromides is described. The protocol has a broad substrate scope that includes electron-rich, electron-deficient and sterically hindered arylboronic acids and heteroaryl bromides. The catalytic activity of the catalyst has been further investigated in the coupling of 2, 6-dibromopyridine with arylboronic acids.